Role of Ayurveda in Delayed Speech in Children – A Case Series - Sabade, Mahesh; Dube, Shanta R (International Research Journal of Ayurveda & Yoga, 2023)
Developmental delay in speech is a common occurrence among young children in India with a prevalence of up to 17%. If left undiagnosed and untreated, speech delay can lead to other adverse developmental and health outcomes. The purpose of this paper is to present unusual cases that showed the uncommon role of Ayurveda in the treatment of speech delay among three separate patient case studies of children aged 24 to 29 months who presented with the inability to formulate words. The ayurvedic concept of speech formation involves the initiation of sound waves from the umbilicus, which travels upward and then eventually gets manifested through vocal cords. Understanding the health of the umbilicus and surrounding anatomical structures in the abdomen was critical in the diagnosis and treatment of the three case studies. The cleansing treatment provided is similar to that given for worm infestation, which has distant similarities in the mechanism of disease as speech delay. In all three cases, the treatments provided led to a gradual increase in word formation and verbalization including the number of words and the sentences spoken. One of the patients demonstrated significant improvement by speaking full sentences and expressing words distinctly, 30-day post-treatment. The other two patients started speaking complete sentences and expressing words by month three post-treatment. The presentation of the three cases provides a unique lens on the use of Ayurveda principles and may provide an alternative approach to treating speech delays that focus more on lifestyle and individual constitution.